Pengaruh Keterlibatan Ayah dalam Pengasuhan (Father Involvement) Terhadap Kepribadian Anak: Penelitian - Ananda Rachmaniar; Syifa Nabila; Muthahharah Thahir; Fajar Maulana Yusup (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A father's role is essential to encourage the growth and development of all aspects of a child's life. The role of fathers in parenting has a huge impact on a child's independence and self-confidence. This study aims to gather valid information on how father involvement affects children's personality. This research method uses a literature study that collects data from 15 journal articles (national and international) that examine how father involvement in parenting affects children's personality. The results showed that father involvement in parenting is very influential for the formation and development of a child's personality. This is obtained from the results of research journal articles which explain that the child's personality will be positively formed and well developed if the father takes part in the child's care. Conversely, if the father is not involved in the child's care, the child will grow up to be an individual who has problems in his personality.